Mechanisms to Inhibit Matrix Metalloproteinase Activity: Where are we in the Development of Clinically Relevant Inhibitors? - Christian A. Corbitt; Jing Lin; Merry L. Lindsey (Recent Patents on Anti-Cancer Drug Discovery, 2007)
Matrix metalloproteinases (MMPs) are involved in numerous pathophysiological processes, including cancer and cardiovascular disease. MMPs proteolyze multiple targets, including extracellular matrix, cytokines, and growth factors. Due to a high clinical relevance, MMPs have long been a target for pharmaceutical intervention. Although numerous drug therapies to inhibit MMPs have been explored, only one agent (doxycycline hyclate) is currently approved for clinical use. Multiple reasons potentially explain the lack of success in developing MMP inhibitors, including issues with selectivity and specificity and the presence of multiple substrates with conflicting functions. Major recent advances in the MMP field include an increased understanding of MMP biology, the improved establishment of parameters to adequately evaluate efficacy, and methods to enhance inhibitor design. This review will explore the latest research and patents targeted at MMP inhibition, and will focus on both direct and indirect mechanisms to block MMPs.
Keywords: MMP inhibitors